2006
DOI: 10.1152/jn.00289.2006
|View full text |Cite
|
Sign up to set email alerts
|

Intersegmental Coordination During Human Locomotion: Does Planar Covariation of Elevation Angles Reflect Central Constraints?

Abstract: Hicheur, Halim, Alexander V. Terekhov, and Alain Berthoz. Intersegmental coordination during human locomotion: does planar covariation of elevation angles reflect central constraints? J Neurophysiol 96: 1406 -1419, 2006. First published June 21, 2006 doi:10.1152/jn.00289.2006. To study intersegmental coordination in humans performing different locomotor tasks (backward, normal, fast walking, and running), we analyzed the spatiotemporal patterns of both elevation and joint angles bilaterally in the sagittal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 29 publications
2
50
2
Order By: Relevance
“…The correlation between foot and shank elevation angles was significantly smaller in quail bipedal locomotion (0.76-0.83) than in both macaque (0.88-0.91) and human (0.94-0.97) bipedal locomotion (P<0.001 for all combinations), indicating that the strong correlation between foot and shank elevation angles observed in humans (Hicheur et al, 2006) was not observed in quails. However, the correlation between thigh and foot elevation angles was significantly larger in quail (0.85-0.95) and macaque (0.76-0.92) bipedal locomotion than in human bipedal locomotion (0.24-0.58; P<0.001 for all combinations), and the correlation between shank and thigh elevation angles was significantly larger in quail (0.61-0.87) and macaque (0.77-0.82) bipedal locomotion than in human bipedal locomotion (0.49-0.69; P<0.001 for all combinations).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The correlation between foot and shank elevation angles was significantly smaller in quail bipedal locomotion (0.76-0.83) than in both macaque (0.88-0.91) and human (0.94-0.97) bipedal locomotion (P<0.001 for all combinations), indicating that the strong correlation between foot and shank elevation angles observed in humans (Hicheur et al, 2006) was not observed in quails. However, the correlation between thigh and foot elevation angles was significantly larger in quail (0.85-0.95) and macaque (0.76-0.92) bipedal locomotion than in human bipedal locomotion (0.24-0.58; P<0.001 for all combinations), and the correlation between shank and thigh elevation angles was significantly larger in quail (0.61-0.87) and macaque (0.77-0.82) bipedal locomotion than in human bipedal locomotion (0.49-0.69; P<0.001 for all combinations).…”
Section: Resultsmentioning
confidence: 72%
“…changes in the orientation of these segments with respect to the vertical axis, covary to form a regular loop within a single plane in three-dimensional space (Borghese et al, 1996;Bianchi et al, 1998;Grasso et al, 1998;Ivanenko et al, 2002;Ivanenko et al, 2005;Ivanenko et al, 2007;Ivanenko et al, 2008;Hicheur et al, 2006;Barliya et al, 2009;Dominici et al, 2010;Ogihara et al, 2012;Sylos-Labini et al, 2013). In humans, the plane can account for more than 99% of the total variance in the elevation angles (Borghese et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Further details of the calculation method employed in this study have been described elsewhere [1,4,8]. To evaluate similarities between pairs of elevation angles, we calculated correlation coefficients as described previously [9]. We also approximated elevation angle profiles using the first Fourier decomposition harmonics to quantify phase shifts between pairs of elevation angles [2,10].…”
Section: Methodsmentioning
confidence: 99%
“…However, biomechanical constraints may also play a part in emergence of the planar law. For example, Hicheur et al [9] suggested that the planar law arises mainly due to the strong coupling of foot and shank movements resulting from a restricted range of ankle joint movement. Barliya et al [10] argued that biomechanical constraints due to biarticular muscles and passive coupling of limb segments may also play a role, although the inter-segmental plane may not emerge only from such biomechanical factors.…”
Section: Introductionmentioning
confidence: 99%
“…We used heel strike and toe off events to define steps [24]. These events were derived from the time course of heel and toe Z position profiles and corresponded to the local minima of these two signals.…”
Section: General Parameters and Stepping Behaviormentioning
confidence: 99%